Volume 2: Fora 2006
DOI: 10.1115/fedsm2006-98271
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Inlet Boundary Layer Thickness on the Rotating Stall in an Axial Compressor

Abstract: A three-dimensional numerical simulation is conducted to study an effect of the inlet boundary layer thickness on the rotating stall in an axial compressor. The inlet boundary layer thickness has significant effects on the hub-corner-separation in the junction of the hub and suction surface. As the load is increased, the size of the hub-corner-separation is increased dramatically for the thick inlet boundary layer but it is diminished to be indistinguishable from the wake of the blade for the thin inlet bounda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…A local time-stepping method based on the Courant-Friedrichs-Lewy number and a message-passing interface (MPI) are used for rapid calculation. The governing equations and descritization methods used in T-Flow are described in detail in Choi (2008).…”
Section: T-flowmentioning
confidence: 99%
“…A local time-stepping method based on the Courant-Friedrichs-Lewy number and a message-passing interface (MPI) are used for rapid calculation. The governing equations and descritization methods used in T-Flow are described in detail in Choi (2008).…”
Section: T-flowmentioning
confidence: 99%
“…The shape factor in the current study is similar to the values obtained by Knezevici et al (2008) and MacIsaac et al (2010) in their turbine cascade studies performed in the same wind tunnel. Choi et al (2008) conducted numerical investigations of the effect of inlet boundary layer thickness on the rotating stall using a low-speed axial compressor rotor blade (NACA 65 profile) at a constant Reynolds number of 244,000 (based on axial chord and inlet velocity at design condition). The investigations showed that, at design condition, the inlet boundary layer thickness had minimal effect on the size of the hub-corner separation.…”
Section: Intensitymentioning
confidence: 99%